Salinity as a determinant factor in morphology and anatomy of mangrove plant Lumnitzera racemosa Willd. - A. K. Rajalakshmi; P. Elavazhahan; P. Manivannan (Innovations in Agriculture)
Along with their ecological significance, the Lumnitzera racemosa Willd. mangrove is interesting for its abundance of natural compounds, some of which have the potential to be used in medicine. In this study the effect of different concentrations of sodium chloride on growth and development of seedlings of L. racemosa was analysed. The growth parameters such as shoot and root length, number of leaves, leaf area, fresh weight and dry mass production increased with increasing sodium chloride upto 500 mM and it can be concluded that, this plant can grow and survive in this salt level.